Liver and/or kidney transplantation in amino and organic acid-related inborn errors of metabolism: an overview on European data - Molema, Femke; Martinelli, Diego; Hörster, Friederike; Kölker, Stefan; Tangeraas, Trine; Koning, Barbara de; Dionisi-Vici, Carlo; Williams, Monique (Journal of inherited metabolic disease, 2021)
Background This study provides a general overview on liver and/or kidney transplantation in patients with an amino and organic acid-related disorder (AOA) with the aim to investigate patient characteristics and global outcome in Europe. This study was an initiative of the E-IMD and the AOA subnetwork of MetabERN. Methods A questionnaire was sent to all clinically active European Society for the Study of Inborn Errors of Metabolism (SSIEM) members. The questionnaire focused on transplanted individuals with methylmalonic acidemia (MMA), propionic acidemia (PA), maple syrup urine disease (MSUD), and urea-cycle disorders (UCDs). Results We identified 280 transplanted AOA patients (liver transplantation in 20 MMA, 37 PA, 47 MSUD, and 111 UCD patients, kidney or combined liver and kidney transplantation in 57 MMA patients and undefined transplantation type in 8 MMA patients), followed by 51 metabolic centers. At a median follow-up of 3.5 years, posttransplant survival ranged between 78% and 100%, being the lowest in PA patients. Overall, the risk of mortality was highest within 14 days posttransplantation. Neurological complications were mainly reported in Mut0 type MMA (n = 8). Nonneurological complications occurred in MMA (n = 28), PA (n = 7), and UCD (n = 14) patients, while it was virtually absent in MSUD patients. Only 116/280 patients were psychologically tested. In all, except MSUD patients, the intelligence quotient (IQ) remained unchanged in the majority (76/94, 81%). Forty-one percentage (9/22) of MSUD patient showed improved IQ. Conclusion The survival in AOA individuals receiving liver and/or kidney transplantation seems satisfactory. Evidence-based guidelines, systematic data collection, and improved cooperation between transplantation centers and European Reference Networks are indispensable to improve patient care and outcomes.
"First published: 30 September 2020".- Frontdoor des Artikels
Gesehen am 12.08.2024